2022
DOI: 10.1097/apo.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy: Role of Neurodegeneration and Therapeutic Perspectives

Abstract: Retinal neurodegeneration plays a significant role in the pathogenesis of diabetic retinopathy, the leading cause of preventable blindness. The hallmarks of diabetes-induced neurodegeneration are neural cell apoptosis and glial activation, which seem even before vascular lesions can be detected by ophthalmoscopic examination. The molecular mediators of retinal neurodegeneration include proinflamma- tory cytokines, oxidative stress, mitochondrial dysfunction, and the molecular pathways closely related to chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 97 publications
1
14
0
Order By: Relevance
“…130 In addition, the streptozotocin-induced neurodegenerative disorder mice model indicates that liposomal citicoline therapy increases pro-inflammatory cytokines NF-κB, TNF-, IL-6, IL-8, and MCP-1. 131,132 All these data confirmed our results that intranasal citicoline significantly reduces NFκB hippocampus tissue levels (Table 5). In this study, the administration of AlCl 3 resulted in learning and memory impairments, and an increase followed this in oxidative stress levels; an increase in hippocampus MDA levels.…”
Section: In Vivo Studysupporting
confidence: 85%
“…130 In addition, the streptozotocin-induced neurodegenerative disorder mice model indicates that liposomal citicoline therapy increases pro-inflammatory cytokines NF-κB, TNF-, IL-6, IL-8, and MCP-1. 131,132 All these data confirmed our results that intranasal citicoline significantly reduces NFκB hippocampus tissue levels (Table 5). In this study, the administration of AlCl 3 resulted in learning and memory impairments, and an increase followed this in oxidative stress levels; an increase in hippocampus MDA levels.…”
Section: In Vivo Studysupporting
confidence: 85%
“…The Consortium for the Early Treatment of DR (EUROCONDOR) study failed to find any signs of neurodegeneration in a significant percentage of patients with microangiopathic retinal lesions[ 66 , 67 ]. However, as already mentioned before, neurodegeneration has been proposed as a hallmark of DR[ 68 - 70 ]. Indeed, the American Diabetes Association (ADA) has classified DR as a microvascular and neurovascular complication[ 29 ].…”
Section: Experimental Data On Mechanisms Underlying the Glp-1ras/reti...mentioning
confidence: 99%
“…Study results suggested that the drug prevents exactly those three features of diabetes-related retinal damage. The mechanism behind this phenomenon seemed to rely on the decisive anti-inflammatory action linked to decreased expression of NF-kB, proinflammatory cytokines (IL-1, IL-6, and IL-18), and ICAM-1, as well as on the prevention of neuroretinal cell apoptosis promoted by the activation of Akt pathway, which is essential for neuron survival[ 70 ]. Moreover, as blood glucose levels were not affected by topical administration, no confounding factors were present due to eventually occurring drops in glucose concentrations.…”
Section: Experimental Data On Mechanisms Underlying the Glp-1ras/reti...mentioning
confidence: 99%
“…Evidence suggests alterations in the normal regulatory mechanisms controlling blood flow occur early in the course of the disease in the diabetic retina, even before pathological structural abnormalities are seen (reviewed by Stitt et al [ 7 ]). This is not surprising considering all components of the neurovascular unit are likely sensitive to the effects of hyperglycaemia [ 15 , 16 ]. A reduction in retinal blood flow, in the context of prolonged transit times through the retinal capillaries [ 17 ], has been documented in individuals with diabetes before the development of overt DR (defined as retinopathy that can be seen on fundus examination or fundus photographs) [ 17 ].…”
Section: Pathogenesis Of Retinal Capillary Drop-out In Diabetesmentioning
confidence: 99%